2011
DOI: 10.2151/sola.2011-050
|View full text |Cite
|
Sign up to set email alerts
|

A General Circulation Model Study of the Impact of a Stratospheric Sudden Warming Event on Tropical Convection

Abstract: The impact of a Northern Hemisphere stratospheric sudden warming (SSW) event on tropical convection is investigated as an initial value problem using a general circulation model. The amplification of planetary waves that produced the simulated SSW was forced by introducing an anomalous field in the model initial conditions. The impact of this SSW event on the tropics was examined by comparing runs with and without the SSW. An increased stratospheric mean meridional circulation cools the tropical lower stratosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 21 publications
3
17
0
Order By: Relevance
“…Our previous numerical experiment also shows that, when local cooling occurs near the tropopause, upwelling enhances, accompanying a warming in the lower TTL and the upper troposphere (see Fig. 4 of Kodera et al, 2011a). A global nonhydrostatic model study (Eguchi et al, 2015) also confirmed the relationship suggested in the present result.…”
Section: Summary and Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our previous numerical experiment also shows that, when local cooling occurs near the tropopause, upwelling enhances, accompanying a warming in the lower TTL and the upper troposphere (see Fig. 4 of Kodera et al, 2011a). A global nonhydrostatic model study (Eguchi et al, 2015) also confirmed the relationship suggested in the present result.…”
Section: Summary and Discussionsupporting
confidence: 89%
“…A possible impact of stratospheric meridional circulation on cumulus heating has been suggested by Thuburn and Craig (2000) in a simplified general circulation model experiment. Stratospheric upwelling effects on tropical convection is also confirmed by a more realistic general circulation model forecast study (Kodera et al, 2011a). These models make use of cumulus parameterization to account for the effect of convection into large-scale circulation.…”
Section: Introductionmentioning
confidence: 60%
“…12d). Previous model studies (Thuburn and Craig, 2000;Kodera et al, 2011) showed that changes in stratospheric meridional circulation affect tropical convective activity through changes in static stability in the tropical tropopause region (Eguchi et al, 2015). In the present experiments also, suppression of equatorial ascending motion occurs in the troposphere in connection with the reduction of stratospheric mean meridional circulation change, as can be seen in the residual circulation differences in Fig.…”
Section: Stratosphere-troposphere Dynamical Coupling Processessupporting
confidence: 80%
“…As a pilot study, simulation data from a global nonhydrostatic model (NICAM), where moist convection is explicitly represented, were analysed. The impact of the SSWs has been confirmed in a previous ensemble mean forecast study of a conventional GCM by implementing a perturbation in the extratropical initial field to produce or to suppress the SSW (Kodera et al, 2011). Note, however, that the cumulus convection is parameterized in this GCM, so that we further need to verify whether similar results are obtained by using a global cloud resolving model.…”
Section: Summary and Discussionsupporting
confidence: 61%
“…Thuburn and Craig (2000) used momentum forcing in a simplified global general circulation model (GCM) to show that a change in the stratospheric meridional circulation modified cumulus heating in the TTL as well as the tropopause height. Kodera et al (2011) constructed a more realistic forecast experiment by incorporating an atmospheric blocking-type circulation anomaly in the North Atlantic in the initial conditions to amplify planetary waves and produce strong BD circulation later in the stratosphere. The results showed similar effects in the tropics to those seen in observational studies; that is, the tropical convective activity was enhanced zonally, especially in the Southern Hemisphere (SH), and cooling at the tropopause region associated with the SSW event was capable of modulating tropical convective activity.…”
Section: Introductionmentioning
confidence: 99%